THE ESSENCE OF THE CONTENT OF STEAM EDUCATIONAL TECHNOLOGY IN THE TEACHING OF ASTRONOMY - Sunnatova U. K. (Web of Journals Publishing, 2023)
STEAM is one of the innovative techniques that is currently the most fundamental tradition of the world education system. One can see that the Steam abbreviation looks very complex, but if we see it separately, we can see that it is simple and clear, namely: S – science, T – technology, E – engineering, a – art, M – mathematics, or natural sciences, technology, engineering arts, creativity, mathematics. Science (Science)-embodies a comprehensive level of training to future specialists from various fields of technology, natural sciences and engineering.
Keywords: Education, system, STEAM, technology, children, model, innovation, like.